ANTI-REFUGEE AND IMMIGRANT REPRESENTATION IN THREE GERMAN ONLINE ILLUSTRATIONS - Liyanti, Lisda; Linati, Fakhrana (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
AbstractSocial criticism is often showed in various forms, one of it is through an illustration. Thus, many people ultimately poured their aspirations, criticism and even innuendo into a drawing. The easy access to the internet today also makes the illustrators take part in doing literary works that are published online. Through the semiotic theory of Ferdinand de Saussure, this paper analyses three online illustrations made by German cartoonists and illustrators; Schwarwel, Harm Bengen, and Freimut Woessner. These three corpuses are published online through their website. The result of this research indicates that the illustrations by Schwarwel, Harm Bengen, and Freimut Woessner represent a rejection of German refugees and immigrant in the political, educational and social sphere.Keywords: Internet, Illustration, Immigrants, Refugees, Representation, Rejection